Ruins: living heritage: Conservation, restoration and enhancement - Frenda, Antonino; Soldano, Silvia; Borlizzi, Patrizia (Protection of Cultural Heritage, 2020)
Ruins are representative of European values and illustrative of European history and heritage and our aim should be to raise awareness of this heritage in order to create a stronger identification with Europe and a further European integration as well. While people are living in and around World Heritage sites, their role in heritage processes and management has changed considerably. Nowadays we must connect the conservation goals with the objective of smart, inclusive and sustainable growth. Local communities must be encouraged to use their local cultural assets as a springboard through a process whereby local actors, are encouraged to assume an active stewardship over the heritage and are empowered develop that heritage in a responsible, profitable and sustainable manner. In their evocative and fascinating image, ruins must be returned to the contemporary life from which they often appear, instead, dramatically separated. Interventions on ruins appear difficult and risky, on the boundary line between archaeological and architectural restoration. The contemporary architectural interventions on the ruin oscillate from conservation to reintegration, up to the absolute extremism consisting in the reconstruction, considered acceptable and suitable only if based on the contemporary design that, from the knowledge of the history, leads to a creative and modern form and image of the architectural work.